Algeria’s strategy to upgrade renewable energies to prepare green economy indicators - Benamrane, Souhiala; Djebli, Sabrina (Journal of Human Sciences, 2021)
The world is heading today to search for renewable and alternative energies that preserve the environment and human health. The emergence of a green economy that aims to achieve economic development by opening environmentally friendly projects linked to renewable energies. By setting up a program to develop renewable energies and energy efficiency. And we will address the extent of efficiency. The strategy adopted by Algeria to achieve a green economy through renewable energy.The study aims to evaluate the procedural, legal and technical policies adopted by the Algerian state in the field of renewable energies and to identify obstacles in the field of development and widespread use of renewable energies as an alternative and indicator of the green economy.The most important results were reached: Algeria is making tremendous efforts in the field of developing and spreading the use of renewable energies, and various levels of progress have been achieved.